2015
DOI: 10.1002/ejoc.201501017
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective [1N+2C+2C] Assembly of Fully Decorated Pyrroles from Primary Amines, 1,2‐Diaza‐1,3‐dienes, and 2,3‐­Allenoates

Abstract: A mild, sequential multicomponent reaction strategy for the regioselective synthesis of functionalized pentasubstituted pyrroles from readily accessible primary amines, 1,2-diaza-1,3-dienes, and 2,3-allenoates, has been developed. The process allows a [1N+2C+2C] annulation to be achieved through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 49 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…All attempts to isolate the first intermediate failed. On the basis of our previous experience, we hypothesized that initially an hydrazonic adduct is formed (Scheme ), which subsequently intramolecularly cyclizes producing the furanic ring. The best result was obtained using CuCl 2 , but the yield was poor (23%, entry 6).…”
Section: Results and Discussionmentioning
confidence: 99%
“…All attempts to isolate the first intermediate failed. On the basis of our previous experience, we hypothesized that initially an hydrazonic adduct is formed (Scheme ), which subsequently intramolecularly cyclizes producing the furanic ring. The best result was obtained using CuCl 2 , but the yield was poor (23%, entry 6).…”
Section: Results and Discussionmentioning
confidence: 99%
“…For instance, Santeusanio reported the synthesis of pentasubstituted hydroxypyrroles 21 by combining 1,2-diaza-1,3-dienes 19, primary amines, and 2,3-allenoates 20. 32 The reaction mechanism is proposed through a conjugate addition of amine to the -carbon of 19, followed by nucleophilic addition to allenoate 20 to produce intermediate 22. Subsequent intramolecular cyclization then affords the hydroxypyrrole product 21.…”
Section: Allenesmentioning
confidence: 99%
“…It has been demonstrated that amines react with azoalkenes A forming α-aminohydrazones (Scheme 1) [3549], however, addition of several azoalkene molecules to amines is virtually unknown. To our knowledge, there is only one report on the formation of bishydrazones as undesirable products in reactions of some primary amines with N -tosylhydrazone of o -bromophenacyl bromide [50].…”
Section: Introductionmentioning
confidence: 99%